(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study presents a needs-based evaluation of Project GLAM (Generating Livelihood through Amazing Make-Up), a community extension intervention implemented by the College of Education of the Nueva Ecija University of Science and Technology (NEUST) in partnership with the Department of Social Welfare and Development (DSWD), local government units, and private-sector partners. The project addresses the documented vulnerability of out-of-school youth (OSY) and students monitored under the Pantawid Pamilyang Pilipino Program (4Ps) by equipping them with marketable competencies in hair styling, make-up artistry, personal grooming, and entrepreneurship. The study synthesizes three primary sources: a DSWD needs assessment of 4Ps case-management data covering nine municipalities in Nueva Ecija; the NEUST Accomplishment and Terminal Report documenting the first wave of training across three pilot sites (Guimba, Quezon, and Talavera) from March 16 to 27, 2026; and the instructional module developed for the beauty care and make-up artistry curriculum. Findings show that poverty-driven child labor (58.9%), financial concern (30.3%), early pregnancy or fatherhood (5.5%), and early marriage (5.3%) were the leading drivers of school dropout among 3,049 identified children, of whom 1,822 were classified as high-risk. The project trained 55 participants across 72 hours of instruction, achieving 100% completion across all logical-framework output indicators and an overall client-satisfaction rating of 4.84 (Excellent, Very Satisfied). Pre-training competency self-ratings rose from 2.46 to 3.44 following the intervention. The evaluation is situated within human capital theory and the capability approach, and is read against Philippine and international literature on TVET effectiveness, conditional cash transfers, and higher-education extension. The study concludes that competency-based, entrepreneurship-integrated beauty and wellness training is a feasible and well-received mechanism for converting short-term conditional cash transfers into pathways toward sustainable, community-based livelihoods, while noting that self-reported, single-source, output-level evidence from a three-site pilot warrants caution in generalizing to outcome-level and program-wide claims. Recommendations include a second wave of training to reach a wider pool of identified high-risk beneficiaries, pursuit of formal TESDA National Certificate II accreditation, establishment of a mobile training unit for remote barangays, and longitudinal tracking of graduate income and employment outcomes.